Thyroid surgery YouTube videos: estimating quality by surgeon characteristics and view rate - Shires, Courtney Brooke (Gland Surg, 2019)
BACKGROUND: With readily available material online we aimed: (I) to estimate the volume of thyroid surgery-related video content readily available to the surgical trainee; (II) to stratify the sources of thyroid surgery-related video content by source (patient, institution, surgeon, or other) and (III) to estimate the quality of the surgeon source by related scholarly output. METHODS: A search of YouTube, a widely used source of open-access video content, was undertaken using “thyroidectomy” as the search term. The first 100 “hits” were analyzed for source. When the video was surgeon-sourced, the surgeon’s name was used in a PubMed author query for “thyroidectomy” and publications noted. RESULTS: Approximately 7,260 videos were returned using “thyroidectomy” as the search term. The first 100 “hits” were stratified by source, assuming the typical surgical trainee would not delve further into the list. The sources were primarily surgeons, followed by patient testimonials, and institutions. The surgeons were stratified by related publications listed in PubMed. The majority of surgeons were not published in thyroid surgery-related topics. CONCLUSIONS: Internet video content is an increasingly utilized source of surgical education. Since video content can be posted without peer review or confirmation of veracity, this study measures the variety of sources of thyroid surgery information. Individuals without thyroid surgery publication history posted the majority of surgeon-sourced video content, although this history serves only as a surrogate for an academic career. Trainees and educators alike should critically analyze the quality of video content.